2008
DOI: 10.1073/pnas.0806133105
|View full text |Cite
|
Sign up to set email alerts
|

NGF and BDNF signaling control amyloidogenic route and Aβ production in hippocampal neurons

Abstract: Here, we report that interruption of NGF or BDNF signaling in hippocampal neurons rapidly activates the amyloidogenic pathway and causes neuronal apoptotic death. These events are associated with an early intracellular accumulation of PS1 N-terminal catalytic subunits and of APP C-terminal fragments and a progressive accumulation of intra-and extracellular A␤ aggregates partly released into the culture medium. The released pool of A␤ induces an increase of APP and PS1 holoprotein levels, creating a feedforward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
127
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 154 publications
(140 citation statements)
references
References 24 publications
12
127
1
Order By: Relevance
“…76 Together, these results also seem to open a new paradigm in the field of NGF intracellular signal transduction, because the same TrkA transmembrane receptor may switch from pro-survival to pro-apoptotic action, in the presence or absence of its physiological cognate ligand. In addition, the evidence that NGF receptors, directly or indirectly, interact with Ab peptide(s) and PS1 in apoptotic neurons and that analogous effects are induced by synthetic Ab exogenously added peptide 53,68 corroborates the ongoing hypothesis of a cellular interplay between the NGF receptors (TrkA and p75) and the amyloidogenic APP processing machinery (Figure 3). 77 …”
Section: Ngf-deprived Hippocampal Neurons: the Amyloid Cascade And Tamentioning
confidence: 51%
See 1 more Smart Citation
“…76 Together, these results also seem to open a new paradigm in the field of NGF intracellular signal transduction, because the same TrkA transmembrane receptor may switch from pro-survival to pro-apoptotic action, in the presence or absence of its physiological cognate ligand. In addition, the evidence that NGF receptors, directly or indirectly, interact with Ab peptide(s) and PS1 in apoptotic neurons and that analogous effects are induced by synthetic Ab exogenously added peptide 53,68 corroborates the ongoing hypothesis of a cellular interplay between the NGF receptors (TrkA and p75) and the amyloidogenic APP processing machinery (Figure 3). 77 …”
Section: Ngf-deprived Hippocampal Neurons: the Amyloid Cascade And Tamentioning
confidence: 51%
“…Thus, even in NGF-deprived hippocampal neurons, we observed that (1) the released Ab extracellular peptides created a neurotoxic loop, because the extent of ensuing cell death was much greater than that expected on the potential number of NGF-responsive target neurons previously found; (2) b-or g-secretase inhibitors -or mixture of both -and Ab antibody, 4G8, largely prevented not only the Ab intra-and extra-production but also neuronal death. 53 The temporal interplay between Ab overproduction and tau protein post-translational modifications was also established from the observation that two specific amino-acidic sites 42 ). (a) CGNs at 6 DIV (upper wells) were transferred in sister cultures kept in S-K25 whereas the correspondent co-cultured neurons (bottom wells) were switched to apoptotic S-K5 medium.…”
Section: Ngf-deprived Hippocampal Neurons: the Amyloid Cascade And Tamentioning
confidence: 99%
“…We observed that primary hippocampal neurons after 48 h of NGF exposure, die following NGF withdrawal, with an increase of APP processing and an intra and extracellular Ab accumulation (Matrone et al, 2008b; Fig. 1).…”
Section: Ngf Signaling and Amyloidogenesismentioning
confidence: 77%
“…We observe that an early, transient and site-specific GSK-3b-mediated tau hyperphosphorylation (3-6 h after NGF withdrawal)-at two AD-relevant pathological epitopes (Ser262 and Thr231)-is temporally and causally related with an activation of the endogenous amyloidogenic pathway in NGF-deprived hippocampal primary neurons (Matrone et al, 2008b). The specific changes of tau phosphorylation state, as well as apoptotic death, are blocked by 4G8 and 6E10 Ab antibodies or by specific b and/or c secretases inhibitors, suggesting that such events are induced by endogenously overproduced Ab.…”
Section: Ngf and Tau Protein Metabolismmentioning
confidence: 82%
“…This is supported by the finding that the AD11 mouse model, which expresses the recombinant monoclonal antibody αD11 that specifically neutralizes NGF thus causing NGF deprivation, shows ADlike pathology including Aβ accumulation and hippocampusdependent memory deficits [63,64] . Based on the report that activation of the amyloidogenic route by NGF deprivation induces apoptotic death in PC12 cells [65] , Matrone and colleagues further found that APP and presenilin 1 N-terminus (which is the active component endowed with γ-secretase activity) levels were increased in hippocampal neurons that were previously exposed to NGF or BDNF for 48 h followed by deprivation by anti-NGF (or -BDNF) antibodies [66] . These findings suggest that Aβ and NTF deficits cause a feedforward loop that accelerates the toxicity of Aβ sufficient to cause neuronal death.…”
Section: Ntf Deficits Cause Aβ Overloadmentioning
confidence: 99%